Pengaruh Desain Kemasan Madu Bedasarkan Model VIEW Terhadap Minat Beli Konsumen (Studi Kasus UMKM Madu Asy-Syifa Babussalam) - Fadjri, Dyah Sekar Taji Nur; Fatimah, Sri; Sadeli, Agriani Hermita; Budiman, Muhammad Arief (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Honey has become a widely found product with a variety of brands, and an attractive packaging design is one way to distinguish a product from its competitors. However, there are still many honey producers who have not optimized the use of packaging as a tool for marketing products, one of them is UMKM Honey Bees Asy-syifa Babussalam. The study aims (1) to analyze the impact of visibility, information, emotional appeal, and workability of Babussalam Asyfa Honey packaging on consumer purchasing interests, and (2) to analyse the influence of Visibility, Information, Emotional Appeal and Workability on the simultaneously buying interest of consumers. The research uses quantitative research methods with double regression analysis taken through surveys and interviews. The sample in this study amounted to 125 respondents who were drawn through purposive sampling because of the large number of populations with the criterion of consumption of pure honey. The results of this study show that visibility, emotional appeal, and workability have a significant influence on purchasing interests, while information and non-information have significant influences on buying interests.